The Influence of Mandatory Halal Certification Decisions and Adaptation Strategies on Operational Decisions of Msmes in Sukmajaya District, Depok City, West Java - Cyka Oktaviani; Balqis Yudhi Putri; Ali Ridho (Best Journal of Administration and Management, 2024)
Amid rapid economic growth, MSMEs play a vital role in Indonesia’s economy, driving local economies and providing employment. However, they face challenges such as increasing competition and the requirement for halal certification, as mandated by Law No. 33 of 2014. Halal certification is crucial for both Muslim consumers and global market competitiveness, often requiring MSMEs to adjust production, management, and operations. Effective adaptation strategies, including changes in production methods and supply chain management, are essential to meet halal standards without compromising efficiency. Research shows that mandatory halal certification and adaptation strategies have a positive and significant influence on the operational decisions of MSMEs in Sukmajaya, Depok, West Java. The mandatory halal certification decision has a positive and significant influence on the operational decisions of MSMEs in Sukmajaya District, Depok, West Java, with a significance value of 0.000 < 0.05. Similarly, adaptation strategies have a positive and significant impact on the operational decisions of MSMEs in Sukmajaya, with a significance value of 0.000 < 0.05, and the coefficient value is 0.888